EVALUASI KINERJA KEPALA DESA DI TINJAU DARI LAPORAN KETERANGAN PERTANGGUNGJAWABAN (LKPJ) TAHUN 2022 DI DESA SIMANDRAOLO - Telaumbanua, Ardin; Ndraha, Ayler Beniah; Waruwu, Suka’aro; Harefa, Peringatan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract. Evaluation is an activity to assess the level of performance of a policy by systematically investigating the effectiveness of the program. Meanwhile, learning evaluation is a continuous process of collecting and interpreting information, in assessing decisions made to design a learning system. This research aims to determine the performance of the Simandraolo Village Head during 2022. To find out how the Simandraolo Village Head's performance has been evaluated in achieving success in his duties and responsibilities during 2022 as reviewed by LKPJ. And to analyze how efforts will be made to improve the Performance Evaluation of the Simandraolo Village Head in the future. This research uses qualitative and descriptive research methods. Data collection in this research was interviews, observation and documentation. The data analysis technique includes three stages, namely data reduction, data presentation, and drawing conclusions. From the research results it can be seen that: (1) The Village Head of Simandraolo is considered good by the Village officials, but the community feels there are shortcomings. Several areas need to be improved, including cooperation, program effectiveness, work knowledge, and responsibilities which are considered unsatisfactory. (2) The Simandraolo Village Head has the authority to lead the Village government. In carrying out development, the Village Head plans by involving deliberation between the government and the Village community, in accordance with aspirations, needs and applicable regulations. (3) To improve the performance of village officials, it is necessary to increase intensive communication between village heads, officials and the community.